Analisis Strategi Pemasaran Menggunakan Digital Marketing Dan Delivery Pada Pelanggan Pisang Crispy Kemeklah - Riska Indriani; Rakhmawati Purba (STIE Bina Karya, 2023)
The development of technology and the demands of the community in increasing creative businesses, MSMEs have developed services for selling their products to consumers by implementing a digital marketing system and delivery orders. This was also carried out by the UKM Kemeklah Tebing Tinggi. This study aims to find out how marketing strategies using digital marketing with delivery services can increase the purchase or sale of Kemeklah Tebing Tinggi crispy banana products. This type of qualitative research uses owner, worker and consumer respondents as well as courier brothers who are involved in sales operations. The results of the study show that the use of Digital marketing can increase orders / sales every month. The marketing strategy by using delivery services also increases consumer orders that cannot buy directly at Kemeklah outlets.